BIOECOLOGY AND SIGNIFICANCE OF SMALL FEATHER GRASS (ARISTIDA PENNATA TRIN.) AND LARGE SELIN (ARISTIDA KARELINA) (Eureka Journal of Agricultural Science & Bio-Innovation, 2025)
Selin is a plant of sandy deserts and semi-deserts. In the deserts of Central Asia, it is often found on loose dunes and small sandy hills, along with calligonum and saksaul. Forms small sandy, micro and macro elevations in some plant communities where the plant cover of sandy deserts is disturbed by anthropogenic impact Five species of selenia grow in the steppes and deserts of the CIS countries. Although selenia does not produce much green mass, it can be used for green fodder and hay in the spring.
Keywords: Desert and semi-desert, forms a community, good sand collector, secondary vegetation cover, fodder reserve, anthropogenic, eats at will, food unit, grazing on a regular basis.